Cytogenetics in the genomic era. Issue 3 (September 2020) - Granada, Isabel; Palomo, Laura; Ruiz-Xivillé, Neus; Mallo, Mar; Solé, Francesc
Abstract: Haematological neoplasms are characterised by the presence of recurrent chromosomal abnormalities, making cytogenetics essential for establishing the diagnosis and prognosis. Chromosome banding analysis is mandatory for chronic myeloid leukaemia, neoplasms with eosinophilia, myelodysplastic syndromes and acute leukaemias. In contrast, in other myeloid neoplasms, chronic lymphocytic leukaemia, non-Hodgkin lymphoma and multiple myeloma, the study must be complemented with fluorescence in situ hybridization and/or microarrays, which can overcome some of the shortcomings of banding analysis to identify potential cryptic alterations or reciprocal translocations. In the genomic era, novel technologies such as next generation sequencing are now being used in clinical routine analysis, since they offer the possibility of studying mutations and copy number alterations in a single study at a higher resolution and/or sensitivity. However, they require highly qualified staff and further standardisation, especially regarding data analysis, thereby limiting their current applicability.